Orbit Representations from Linear mod 1 Transformations - Carlos Correia Ramos; Nuno Martins; Paulo R. Pinto (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
We show that every point $x_0in [0,1]$ carries a representationof a $C^*$-algebra that encodes the orbit structure of thelinear mod 1 interval map $f_{eta,alpha}(x)=eta x +alpha$. Such $C^*$-algebra is generated by partial isometries arising from the subintervals of monotonicity of the underlying map $f_{eta,alpha}$. Then we prove that such representation is irreducible. Moreover two such of representations are unitarily equivalent if and only if the points belong to the same generalized orbit, for every $alphain [0,1[$ and $etageq 1$.